Interpersonal Skills Program Based on Artistic Expressions to Reduce Intimate Partner Violence in University Students - Campos Cornejo, Lilia Lucy; Ramírez Montaldo, Rosalinda; García Ampudia, Lupe; Jaimes Campos, Miguel Angel; Sánchez-Chero, Manuel; Villavicencio Guardia, María del Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article evaluated the effects of an interpersonal skills program based on artistic expressions to reduce intimate partner violence in college students. The research was of explanatory type, quasi-experimental design and used the Dating Abuse questionnaire (adapted by Osorio, 2014), the Interpersonal Skills questionnaire with reliability of 0.81 having as results in the entry test in terms of violence a mean of 88. 16 and after the program was applied it decreased to 81.2, in interpersonal skills the mean of 46.6 increased to 53.3 with large effect size according to Cohen's d 7.889 CI95% (6.246-9.532), statistically significant differences were found in terms of violence.